2012
DOI: 10.1093/eurheartj/ehs013
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of QRS morphology and mechanical dyssynchrony to long-term outcome following cardiac resynchronization therapy

Abstract: Non-LBBB patients with dyssynchrony had a more favourable long-term survival than non-LBBB patients who lacked dyssynchrony. Mechanical dyssynchrony and QRS morphology are associated with outcome following CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…A recent single-center analysis showed that RBBB patients who demonstrated evidence of LV mechanical dyssynchrony by speckle-tracking radial strain or interventricular mechanical delay did benefit from CRT. 83 This finding seems supported by data showing that a long Q-LV time predicts a good CRT response, even for patients with RBBB ( Figure 7). 54 These data emphasize the importance of accurate tailoring pacing therapy (LV site providing long Q-LV, and timing of pacing) in RBBB patients to achieve the best possible resynchronization.…”
Section: Patients With Rbbbsupporting
confidence: 55%
“…A recent single-center analysis showed that RBBB patients who demonstrated evidence of LV mechanical dyssynchrony by speckle-tracking radial strain or interventricular mechanical delay did benefit from CRT. 83 This finding seems supported by data showing that a long Q-LV time predicts a good CRT response, even for patients with RBBB ( Figure 7). 54 These data emphasize the importance of accurate tailoring pacing therapy (LV site providing long Q-LV, and timing of pacing) in RBBB patients to achieve the best possible resynchronization.…”
Section: Patients With Rbbbsupporting
confidence: 55%
“…17 For speckle tracking radial strain, 8 digital grayscale 2 dimensional (2D) cine loop images were acquired at end-expiratory apnea from basal and mid-LV short-axis views with frame rates of 60 to 90 Hz for offline analysis (GE EchoPac BT08-BT11). 8,18,19 In brief, circular regions of interest were placed on the endocardial and epicardial borders and manually adjusted for optima time-strain curves. The times to peak strain from 8 free-wall segments (4 from each view) were determined from a minimum of 3 consecutive beats and averaged.…”
Section: Echocardiographymentioning
confidence: 99%
“…Hara et al 27 showed that patients with dyssynchrony had more favorable long-term survival than those without dyssynchrony after CRT. The important finding was that clinical outcomes of patients with significant dyssynchrony were more favorable than those of patients without dyssynchrony.…”
Section: Clinical Outcomesmentioning
confidence: 99%